Study of Probe Distribution for Furnace Acoustic Tomographic Temperature Measurement - Lifeng ZHANG; Yu MIAO (发电技术)
The two/three-dimensional distribution image of furnace temperature can be obtained by furnace acoustic tomographic temperature measurement system. The distribution of ultrasonic probes will directly affect its imaging accuracy. Four-side and four-corner distribution of 8, 12 and 16 ultrasonic probes were studied, respectively. Tikhonov regularization algorithm was adopted to obtain the temperature distribution under coarse mesh, and then the local weighted regression method was used to predict the temperature distribution after mesh refinement. Typical temperature field distributions reconstruction was carried out for the 6 probe distributions, and the root mean square error and correlation coefficient were analyzed. The results show that the highest accuracy can be obtained using 16 four-side distribution probes.